Peningkatan Hasil Belajar Kelas 8-F SMPN 1 Bagor pada Materi Cahaya dan Alat Optik Menggunakan Model Pembelajaran PjBL - Hariyanti, Kartika Syarifah Fitri; Krisdiana, Ika; Trianawati, Eny (Paedagogie, 2023)
The research that has been done aims to find out whether there is an increase in learning outcomes in the material of light and optical devices for class 8-F SMPN 1 Bagor. This article is the result of Collaborative Classroom Action Research which consists of 2 cycles. This Collaborative CAR has one sample, namely 31 students in class 8-F of SMPN 1 Bagor. Collaborative CAR uses the posttest instrument to obtain data on learning outcomes, then calculates the average value and the percentage of completeness of learning outcomes where if it has reached 75% with a value of ≥70 then it is considered to have been achieved or completed. Based on the results of the study it was found that the first cycle of the study obtained an average learning result of 68.33 with a completeness percentage of 56.67%. In cycle 2 of the research, learning improvements were carried out so that an average learning result was obtained at 92.5 with a completeness percentage of 96.67%, which means that the research was said to have been successful. Keywords: Collaborative CAR, PjBL Model, Learning Outcomes